2014
DOI: 10.1016/j.taap.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin inhibits Cr(VI)-induced malignant cell transformation of human lung epithelial cells by targeting ROS mediated multiple cell signaling pathways

Abstract: Hexavalent chromium [Cr(VI)] is a well-known human carcinogen associated with the incidence of lung cancer. Inhibition of metal induced carcinogenesis by a dietary antioxidant is a novel approach. Luteolin, a natural dietary flavonoid found in fruits and vegetables, possesses potent antioxidant and anti-inflammatory activity. We found that short term exposure of human bronchial epithelial cells (BEAS-2B) to Cr(VI) (5 μM) showed a drastic increase in ROS generation, NADPH oxidase (NOX) activation, lipid peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 93 publications
3
69
0
Order By: Relevance
“…c o m / l o c a t e / i n t i m p that increased epithelial/endothelial cell apoptosis contributed to the endothelial and epithelial injury which was the key feature of ALI/ARDS in humans. Previous studies showed that apoptosis inhibitors increased survival rates in rodent models of ALI [8].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 92%
“…c o m / l o c a t e / i n t i m p that increased epithelial/endothelial cell apoptosis contributed to the endothelial and epithelial injury which was the key feature of ALI/ARDS in humans. Previous studies showed that apoptosis inhibitors increased survival rates in rodent models of ALI [8].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 92%
“…This molecule has received extensive attention because of its antiinflammatory17, antioxidative18, and anticarcinogenic19 activities. Increasing evidence has indicated that luteolin might modulate the homeostasis between oxidants and antioxidants, and reduce reactive oxygen species (ROS) production and apoptosis18.…”
mentioning
confidence: 99%
“…[9][10][11] Although studies on isorhamnetin have reported its anti-cancer efficacy, direct effects on HIF-1α regulation have not been identified. In this study, we observed that isorhamnetin inhibited HIF-1α following induction of HIF-1α accumulation in HCT116 and HT29 cells using hypoxia or CoCl 2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…9) Luteolin can inhibit free radicals in the bronchial epithelial cells, which decreases HIF-1α. 10) In addition, quercetin can suppress HIF-1α-dependent transcriptional activity in hypoxic colon cancer cells.…”
mentioning
confidence: 99%